'Every day is a challenge': Expatriate acculturation in the United Arab Emirates. (December 2021) - Thirlwall, Alison; Kuzemski, Dawn; Baghestani, Mahshid; Brunton, Margaret; Brownie, Sharon
The United Arab Emirates (UAE) has a very small population of national citizens, so it relies on foreign workers who bring a range of cultures with them, resulting in a unique multi-cultural context. Unlike Western countries, such as the UK, Canada and Australia, workers are unable to permanently migrate to the UAE, so instead they hold temporary, expatriate status. This exploratory study focuses on the experiences of internationally qualified, expatriate nurses in hospitals in Al Ain, gathered by qualitative interviews. Twenty-one registered nurses participated in this study. The nurses faced challenges associated with language requirements and differing cultural expectations, and displayed limited acculturation, which compromised their ability to provide appropriate care for patients. The temporary nature of the work, cultural expectations, language difficulties and potential improvements are discussed. The findings have important implications for organizations that employ large groups of staff from overseas in all sectors. This article contributes to knowledge of expatriates' challenges in the UAE and highlights the difficulties of working in a diverse environment, leading to a range of actions being recommended for managers.